Male And Female Teachers’ Perspectives on Gender Roles In Early Childhood Education - Putri, Pipin Afindra; Adriany, Vina; Yulindrasari, Hani; Dahlan, Tina (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2024)
This study aimed to explore male and female teachers’ perspectives on gender roles in early childhood education and care settings (ECCE). ECCE is often regarded as one of the most gendered spaces that perpetuate binaries between boys and girls. This research adopted a case study approach conducted in a kindergarten in Padang, Indonesia. The study involved two ECCE teachers as participants, one male and one female. This study's results indicate that teachers understand the importance of gender equality in children. However, they still perceive gender as something biological, limiting seeing children as girls and boys. Teachers seem to be confused about the fluidity of gender roles, and hence, it results in resistance to teaching gender-flexible pedagogy